Understanding the Mechanisms of Main Bronchial Compression in Patients with Intracardiac Anomalies - Makoto Ando, MD, PhD; Takako Nishino, MD, PhD (Annals of Thoracic Surgery Short Reports, 2024)
Background: The study focuses on vascular compression of the main bronchus in the aortopulmonary space, examining potential contributors within the same axial plane. Its goal is to uncover mechanisms of bronchial compression in patients with intracardiac anomalies and review surgical outcomes, aiming to enhance future results. Methods: The morphology and topology of structures within the axial plane of the aortopulmonary space were objectively analyzed, including the sternum, ascending aorta, heart, pulmonary artery, descending aorta, and other relevant elements. Identified deviations from the normal configuration were systematically identified. Operative procedures included mobilizing and removing the compressing vessel, followed by suspending the airway wall to a rigid prosthesis (external stenting), vertebra, or ascending aorta. Results: Computed tomography revealed potential factors contributing to bronchial stenosis, including anteriorly deviated descending aorta (20 patients), dilated pulmonary artery (6), cardiomegaly (12), flat chest (7), funnel chest (3), posteriorly deviated ascending aorta after arterial switch operation (3), low aortic arch (3), and aberrant subclavian artery (2). Kaplan-Meier analysis demonstrated operative survival rates of 96% at 1 year, 87% at 5 years, and 80% at 8-15 years. Ten-year follow-up computed tomography after external stenting procedure revealed the narrowest diameter of the stented bronchus as 94.4% of the reference. Conclusions: Consistent long-term airway patency was observed post-surgery. While the pulmonary artery and descending aorta exert direct compressive effects in most cases, various other potential mechanisms may contribute to bronchial compression. Identifying and addressing these factors through a multidisciplinary approach is crucial for sustaining bronchial patency and preventing complications.